Community structure of deep fjord and shelf benthic fauna receiving different detrital kelp inputs in northern Norway. (February 2021) - Ramirez-Llodra, Eva; Pedersen, Torstein; Dexter, Karen Filbee; Hauquier, Freija; Guilini, Katja; Mikkelsen, Nina; Borgersen, Gunhild; Van Gyseghem, Margo; Vanreusel, Ann; Vilas, Daniel
Abstract: Kelp forests produce large amounts of macroalgal detritus, ranging from whole plants to small particles (1 mm). The role of this kelp detritus in fueling deep-sea communities adjacent to healthy kelp forests was investigated in a region in the north of Norway by comparing the community structure and biodiversity of meio-, macro-, and megafauna in two deep (450 m) areas with different expected input of kelp detritus: a deep fjord basin surrounded by kelp forests and the adjacent continental shelf 15 km offshore from the kelp forests. The results showed that, although the fjord received a significantly higher amount of large kelp detritus (i.e. blades) than the shelf area, the amount of small kelp detritus available on the sediment was similar in both areas. There were significant differences in the multidimensional scaling analyses on the community structure for meio-, macro-, and megafauna between the fjord and the shelf. Significant differences were also found in biomass, abundance and biodiversity indices for some groups. However, no clear pattern emerged in the community structure and biodiversity between the fjord and the shelf, and the observed differences could not be linked directly to kelp detritus availability. The similar amounts of small particles of kelp detritus in the fjord and shelf area suggest that kelp detritus can provide organic matter to ecosystems further away than initially hypothesized, thus potentially shaping the structure and functioning of deep benthic communities distant from the kelp forests. Yet, the direct (trophic) links of kelp detritus and the studied benthic fauna need to be further analysed. The results are discussed in relation to current global changes in kelp forest, including regime shifts from healthy kelp reefs to turfs or barren areas, which reduce drastically the amount of macroalgal detritus produced and exported. Highlights: Large kelp detritus (blades) was observed in a deep fjord basin adjacent to the kelp forest. Small-particle kelp detritus reaches the deep seabed 15 km offshore. Meio, macro and megabenthos communities from fjord and shelf area were different. But no direct explanation could be related to kelp detritus. Small-particle detritus can play an important role in shaping benthic communities.